U.S. dollar risk premiums and capital flows - Balakrishnan, Ravi; Tulin, Volodymyr (IMF working paper ;, 2006)
This paper sheds light on the attractiveness of U.S. assets by studying dollar risk premiums, calculated using Consensus exchange rate forecasts, and linking them to bilateral capital flows. The paper finds that the presence of negative dollar risk premiums (i.e. expectations of a dollar depreciation net of interest rate effects) amid record capital inflows could suggest that investors may favor U.S. assets for structural reasons. One possible explanation could be that the Asian crisis created a large pool of savings searching for relatively riskless investment opportunities, which were provided by deep, liquid, and innovative U.S. financial markets with robust investor protection. Moreover, the continued attractiveness of U.S. financial markets to European investors suggests that they offer a large array of assets, with different risk/return characteristics, that facilitate the structuring of diversified investment portfolios. Looking forward, this suggests that the allocative efficiency of U.S. financial markets could mitigate risks of a disorderly unwinding of global current account imbalances.